UNI EROPA: TELAAH KRITIS ANTARA PENCAPAIAN KEPENTINGAN NASIONAL DAN KEPENTINGAN KAWASAN - Denada Faraswacyen L. Gaol (Transnasional, 2018)
The purpose of this paper is to critically examine the tendency of some countries to step out of EU membership, especially after UK exits from EU membership after the referendum process. To that end, the authors argue that the condition represents the reality that the significance of current national interest is more than the importance of integration in the region. The problem is studied using several concepts such as neorealism and national interest. The result of the analysis by the authors shows that the issue of nationalism tends to be stronger than the integration issue. The EU focuses more on expanding membership rather than on strengthening the implementation of the various agreements that have been made. The basic purpose of EU establishment has the potential to shift due to the behavior of prioritizing EU arrogance over the achievement of the ideals contained in the Maastricht Treaty. Therefore, it can be concluded that political factors are still dominant in decision making in the EU. The less than optimal embodiment of the Maastricht Treaty has led to the emergence of several countries' options to get out of the EU. They perceive that their national interests were not accommodated through European integration.